Comparative Bioavailability Study with Two Pantoprazole Delayed-released Tablet Formulations Administered with and without Food in Healthy Subjects - Fabiana, Mendes D; Anil, Patni K; Simrit, Reyer; Tausif, Monif; Leonard, Moreira D; Jaime, Ilha O; Gustavo, Mendes D; Gilberto, Nucci De (Arzneimittelforschung, 2008)
To assess the comparative bioavailability of two formulations (40 mg delayed-released [DR] tablet; test and reference) of pantoprazole (CAS 102625-70-7) in healthy volunteers of both sexes, with and without food.The study was conducted using an open, randomized, two-period crossover design with a 1-week washout interval, in two groups, with and without food. Plasma samples were obtained for up to 24 h post dose. Plasma pantoprazole concentrations were analyzed by liquid chromatography coupled to tandem mass spectrometry (LC-MS-MS) with positive ion electrospray ionization using multiple reactions monitoring (MRM). From the pantoprazole plasma concentration vs. time curves, the pharmacokinetic parameters AUClast and Cmax were obtained, with and without food.The limit of quantification was 5 ng/mL for plasma pantoprazole analysis. The geometric mean and 90% confidence interval CI of test/reference percent ratios were, without and with food, respectively: 104.6540% (90.8616%–120.5401%) and 99.9708% (90.9987%–l09.8275%) for Cmax, 95.6634% (85.2675%–107.3267%) and 89.3500% (83.6630%–95.4237%) for AUClast.Since the 90% CI for AUClast and Cmax ratios were within the 80–125% interval proposed by the US FDA, it was concluded that pantoprazole 40 mg DR tablet (test formulation) with and without food was bioequivalent to the reference 40 mg DR tablet for both the rate and extent of absorption.
Keywords: CAS 102625-70-7; Pantoprazole, bioavailability, bioequivalence, effect of food; pharmacokinetics, quantification method; Proton pump inhibitors